Syshunt: Game Quiz Mobile untuk Pengenalan Perangkat Keras Komputer menggunakan Successive Approximation Model - Suryadila, Lusi; Ismanto, Edi; Novalia, Melly; Syahfutra, Wandi (Universitas Hamzanwadi, 2025)
Game-based learning media is an example of ongoing technological advances in education. This media is becoming increasingly popular as an innovative solution in education. This research aims to develop and test the feasibility of mobile-based quiz games as learning media for computer hardware introduction using the Successive Approximation Model (SAM). This research is a kind of development using the SAM model. The three main stages of the SAM model consist of the preparation stage, the iterative design stage, and the iterative development stage. The data collection technique in this study used a questionnaire. Meanwhile, the data analysis technique used descriptive quantitative. The result of our findings is a mobile-based quiz game as a learning medium for computer hardware introduction. The results of media and material expert validation show that this game has a media feasibility of 87.14% and material feasibility of 86%. However, the results of the student practicality test were slightly lower with a score of 79.88%, which may be influenced by limitations in the interface features or the time needed for students to adapt to the game mechanics. Nevertheless, the game proved to be effective in understanding computer hardware and is more interactive and fun compared to conventional learning. With a more engaging learning experience, this game can be a creative alternative that supports the teaching and learning process, overcoming the problems of traditional learning that is often monotonous.